A música como apresentação simbólica da sapiência em Hugo de São Vitor - Leão, Fagner da Silva Martins (2019)
In this work, music is presented in two aspects: as a way and symbol of the Creator. Through it, man sees himself in condition of contemplating the Creator, who is referred to by Hugh of Saint Victor as the Sapienza, the divine Logos, Whom man aspires in view of His nature and origin in the very Logos. Hugh of Saint Victor demonstrates, through his philosophical and theological line, a close connection with classical thought, bridging the gap between patristics and scholasticism; he presents us an itinerary of human formation that intends to lead the individual to encounter the Sapientia. In this context, music is considered one of the tools of conduction to the Logos, but it is important to emphasize that the definition of music referred to in the present work is of Greek origin, with a metaphysical character, capable of transcending man, a music that involves everything that exists. Starting from the understanding of the concept of music by Hugh of Saint Victor, the present work points out Gregorian chant as an effective instrument that contains great potential to lead and present the Logos/Sapienza.